Investigating risk factors for urine culture contamination in outpatient clinics: A new avenue for diagnostic stewardship - Patrick S. Whelan; Alicia Nelson; Christopher J. Kim; Christian Tabib; Glenn M. Preminger; Nicholas A. Turner; Michael Lipkin; Sonali D. Advani (Cambridge University Press, 2022)
Mixed flora in urine cultures usually occur due to preanalytic contamination. In our outpatient urology clinic, we detected a high prevalence of mixed flora (46.2%), which was associated with female sex and older age. Patient education did not influence the rate of mixed flora. Future efforts should target high-risk patients.